The Effectiveness of the Mindfull, Meaningfull, Joyfull Learning Approach Based on Cognitive Science in the Digital Learning Framework - Resa, Asmirinda; Syarah, Evi; Inayah A.M, Muh.; Anas, Munawir; Ampry, Evy Segarawati; Hasanah, Uhwah; Meivawati, Eli (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
This study aims to analyze the effectiveness of a cognitive-science-based instructional strategy through the integration of mindful, meaningful, and joyful learning within the framework of digital learning. The research employed an experimental design involving two groups of students—30 in the control group and 30 in the experimental group—supported by qualitative data obtained from teacher and student interviews as well as digital classroom observations. The results indicate a significant improvement in conceptual understanding in the experimental group (mean gain = 14.23) compared to the control group (mean gain = 3.12; p < 0.05), along with an increase in learning motivation (mean gain = 13.12 vs. 3.05; p < 0.05). Qualitative findings reinforce the quantitative results, showing that teachers found it easier to design interactive learning activities, students perceived the learning process as more meaningful and enjoyable, and they were more motivated to engage in discussions and reflective awareness activities. The study concludes that integrating mindful, meaningful, and joyful learning into digital learning is effective in enhancing both cognitive and affective aspects simultaneously and holds strong potential for broader application in developing holistic and humanistic digital pedagogy